MICROTREMOR DYNAMICS RESPONSE ANALYSIS AT MOUNT BOHONG, BANDUNG REGENCY USING HORIZONTAL-TO-VERTICAL SPECTRAL RASIO (HVSR) METHOD - Eridani, Alfa
Mount Bohong is one of the hills located on the border of West Bandung Regency and Cimahi City, West Java. In this area, a tunnel was constructed which involved blasting in its construction. As a result, the surrounding houses were damaged. This shows that this area has a fairly large seismic vulnerability. Therefore, it is necessary to determine the response to seismic dynamics in the Mount Bohong area, one way is by measuring microtremor. On 23 – 27 May 2021, 35 microtremor measurements were carried out which were then processed using the Horizontal-to-Vertical Spectral Ratio (HVSR) method. HVSR is a method that compares the Fourier spectrum of the horizontal component to the vertical component of a single station data to obtain subsurface information. The result of HVSR is a curve containing dominant frequency and amplification. Seismic vulnerability index is a value that can estimate the damage caused by seismic activity. This index can be calculated using the dominant frequency and amplification values. Shear strain is the ability of a material, such as a layer of soil, to stretch or shift during an earthquake. This value can indicate phenomena that may occur in the soil. The values of dominant frequency, amplification, seismic susceptibility index, and shear strain were then mapped respectively. The dominant frequency map shows values in the range 1.28 – 9.23 Hz with high frequencies generally located at the peak of Mount Bohong. The higher the dominant frequency value, the thinner the sediment layer. The amplification map shows values in the range 1.06 – 7.85 with high values found in the southern, western, and northeastern parts of the peak of Mount Bohong. The seismic vulnerability index map shows values in the range of 0.27 – 18.41 with high values located in the southern, western, and northeastern parts of the peak of Mount Bohong. The shear strain obtained at Mount Bohong ranges from 0.00037 to 0.026.